A study on knowledge and perception of HPV infection and vaccination amongst medical students, Barabanki - Verma, Vijayshree; Singh, Vaibhav; Verma, Lawanya; Srivastav, Ankur; Mishra, Sandhya (International Journal Of Community Medicine And Public Health, 2022)
Background: Cervical cancer is third most common cancer in women worldwide and fourth leading cause of cancer deaths in women.in India it’s a leading cancer in women responsible for more than 74,000 deaths per year. To assess knowledge, attitude towards HPV infection and HPV vaccination. Methods: Cross sectional study which was conducted at Mayo institute of medical sciences, Barabanki in January 2022. 150 medical students aged between 18-23 years were included in study. Results: The survey sample consisted of 150 medical students aged between 18-23 years with a mean age of 20.56±1.67 years. Around 22 (14.66%) of responders achieved a total knowledge score of 15 or higher, meaning that they correctly answered more than 15 out of 20 knowledge questions on HPV. Conclusions: There is an urgent need for educational Intervention both formal and informal, not only for girls and boys but also for parents to change their attitude towards HPV vaccination.